The individual and combined effects of snowmelt timing and frost exposure on the reproductive success of montane forbs. (5th March 2019) - Pardee, Gabriella L.; Jensen, Isaac O.; Inouye, David W.; Irwin, Rebecca E.
Abstract: Changes from historic weather patterns have affected the phenology of many organisms world‐wide. Altered phenology can introduce organisms to novel abiotic conditions during growth and modify species interactions, both of which could drive changes in reproduction. We explored how climate change can alter plant reproduction using an experiment in which we manipulated the individual and combined effects of snowmelt timing and frost exposure, and measured subsequent effects on flowering phenology, peak flower density, frost damage, pollinator visitation and reproduction of four subalpine wildflowers. Additionally, we conducted a pollen‐supplementation experiment to test whether the plants in our snowmelt and frost treatments were pollen limited for reproduction. The four plants included species flowering in early spring to mid‐summer. The phenology of all four species was significantly advanced, and the bloom duration was longer in the plots from which we removed snow, but with species‐specific responses to snow removal and frost exposure in terms of frost damage, flower production, pollinator visitation and reproduction. The two early blooming species showed significant signs of frost damage in both early snowmelt and frost treatments, which negatively impacted reproduction for one of the species. Further, we recorded fewer pollinators during flowering for the earliest‐blooming species in the snow removal plots. We also found lower fruit and seed set for the early blooming species in the snow removal treatment, which could be attributed to the plants growing under unfavourable abiotic conditions. However, the later‐blooming species escaped frost damage even in the plots where snow was removed, and experienced increased pollinator visitation and reproduction. Synthesis. This study provides insight into how plant communities could become altered due to changes in abiotic conditions, and some of the mechanisms involved. While early blooming species may be at a disadvantage under climate change, species that bloom later in the season may benefit from early snowmelt, suggesting that climate change has the potential to reshape flowering communities. Abstract : This study provides insight into how plant communities could become altered due to changes in abiotic conditions, and some of the mechanisms involved. While early blooming species may be at a disadvantage under climate change, species that bloom later in the season may benefit from early snowmelt, suggesting that climate change has the potential to reshape flowering communities.